2007
DOI: 10.1016/j.bbmt.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Posttransplant Thrombopoiesis Predicts Survival in Patients Undergoing Autologous Hematopoietic Progenitor Cell Transplantation

Abstract: The frequency and clinical significance of secondary thrombocytopenia following initial engraftment in autologous hematopoietic progenitor cell transplantation (HPCT) is unknown. An institutional review board approved retrospective study of thrombopoiesis was performed in 359 patients transplanted with autologous blood (97%) or marrow (3%) who achieved platelet engraftment to >50,000/microL. Idiopathic secondary posttransplant thrombocytopenia (ISPT) was defined as >50% decline in blood platelets to <100,000/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
3
9
1
Order By: Relevance
“…A significant proportion of our patients (n ¼ 30, 35.7%) developed a secondary decline in plt counts post transplantation. A similar observation was made by Ninan et al 26 in their study, in which the incidence of secondary thrombocytopenia was put at 17%, but their study was carried out in different groups of patients with various hematological malignancies who had AHSCT (18 cases of acute leukemias out of 62 patients). Also, the study by Bruno et al 27 on various malignancies reported an incidence of 19% among their autologous transplant patients.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…A significant proportion of our patients (n ¼ 30, 35.7%) developed a secondary decline in plt counts post transplantation. A similar observation was made by Ninan et al 26 in their study, in which the incidence of secondary thrombocytopenia was put at 17%, but their study was carried out in different groups of patients with various hematological malignancies who had AHSCT (18 cases of acute leukemias out of 62 patients). Also, the study by Bruno et al 27 on various malignancies reported an incidence of 19% among their autologous transplant patients.…”
Section: Discussionsupporting
confidence: 75%
“…26,27,[39][40][41] The immunological mechanism was explored by Ninan et al 26 in their study, but it did not show any autoimmune basis in their patients, neither was there any response in the plt counts with i.v. Ig administration.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations